Estratégias para marcação de moléculas bioativas: síntese de compostos fluorescentes e radiomarcados com flúor-18 - Soraya Maria Zandim Maciel Dias Ferreira (2015)
Positron Emission Tomography and Fluorescence imaging are molecular imaging techniques that enable the characterization and measurement of biologic processes at the cellular and molecular levels. Molecular imaging is showing enormous usefulness in the areasof biochemical, biology, drug discovery, diagnosis and therapy. Our goal in this work was to label bioactive molecules with uorine-18 or with a coumarin prouorophore, aiming to develop probes with potential application in imaging processes. Since antitumoral activitywas reported for some uorinated alkyltriazoles, the radiosynthesis of these compounds was performed by replacing 19F for 18F on their structures in two steps: rst, the bimolecular nucleophilic substitution reaction with [18F]uoride; and subsequently, the click reaction ofthe resultant intermediates with 4-pentyn-l-ol in the presence of Cu(I). For the radiosynthesis, a new fully automated method was developed using the TracerLab MX FDG synthesizer module. In adittion, the peptide UBI 31-38 was synthesized by means of solid phase peptidesynthesis, and then, conjugated with a coumarin prouorophore via the click reaction. The reduced size of UBI 31-38, combined with its strong antimicrobial activity, make this compound a promising candidate for the diagnosis of infections or antimicrobial therapy. Theazidocoumarin was chosen as prouorophore owing to its favorable photophysical properties, small size, biocompatibility and its ability to be easily manipulated synthetically. The click reaction was used as labelling strategy in both cases due to its speed, selectivity, the highyields and versatility. Some of the synthesized compounds were screened for their biological activity. Notably, the peptide-coumarin conjugate exhibited strong antifungal activity against a set of strains of Captococcus neofonnans and Captococcus gattii, including a uconazole resistant strain.